Loop-mediated isothermal amplification combined with lateral flow biosensor for rapid and sensitive detection of monkeypox virus - Huang, Xiaolan; Xiao, Fei; Jia, Nan; Sun, Chunrong; Fu, Jin; Xu, Zheng; Cui, Xiaodai; Huang, Hui; Qu, Dong; Zhou, Juan; Wang, Yi (Frontiers in Public Health, 2023)
The ongoing outbreak of the monkeypox, caused by monkeypox virus (MPXV), has been a public health emergency of international concern, indicating an urgent need for rapid and sensitive MPXV detection. Here, we designed a diagnostic test based on loop-mediated isothermal amplification (LAMP) and nanoparticle-based lateral flow biosensor(LFB) for diagnosis of MPXV infection, termed MPX-LAMP-LFB. A set of six LAMP primers was designed based the ATI gene of MPXV, and LAMP amplification of MPXV templates was performed at 63ºC for only 40 min. The results were rapidly and visually decided using the LFB test within 2 min. The MPX-LAMP-LFB assay can specifically detect MPXV strains without cross-reaction with non-MPXV pathogens. The sensitivity of the MPX-LAMP-LFB assay is as low as five copies of plasmid template and 12.5 copies of pseudo virus in human blood samples. The whole process of the MPX-LAMP-LFB assay could be completed 1h, including rapid template preparation (15 min), LAMP reaction (40 min) and result reporting (< 2 min). Collectively, MPX-LAMP-LFB assay developed here is a useful tool for rapid and reliable diagnosis of MPXV infection.